Islamic Family Law Reform in Indonesia, Türkiye, and Tunisia: A Pierre Bourdieu Perspective - Maulana, Moch. Ahsin (Sakina: Journal of Family Studies, 2026)
This research is motivated by the tension between the modernization of Islamic family law and the resistance of conservative groups in Muslim-majority countries. The primary research problem examines how the sociological and intellectual backgrounds of reformist actors influence the reception and implementation of law in Indonesia, Türkiye, and Tunisia. The novelty of this study lies in the application of Pierre Bourdieu’s Social Practice Theory to dissect the dynamics of legal reform, an approach that transcends conventional textual analysis by highlighting the role of human agency. The research method is qualitative with a comparative study approach. The data corpus is derived from historical literature, the biographies of central figures such as Kartini, Rohana Kudus, Mustafa Kemal Atatürk, and Habib Bourguiba, as well as formal legal manuscripts including Indonesia’s 1974 Marriage Law, the Turkish Civil Code, and the Tunisian Code of Personal Status. Bourdieu’s theoretical lens is used to analyze the interconnectedness between habitus (mental disposition), capital (cultural and symbolic capital), and field (the arena of legal contestation). Comparative findings indicate three primary patterns: radical secularization in Türkiye which abolished Islamic law, progressive state-led ijtihad in Tunisia that prohibited polygamy, and a gradual-dialectic in Indonesia that synthesized religious law with state administration. This study concludes that the success of legal reform depends heavily on the actors’ ability to capitalize on symbolic capital to transform social habitus. <!–a=1–>